Effect of product innovation on purchase decisions mediated by brand image at PT Pegadaian - Fajar, Alfan; Purmono, Bintoro Bagus; Afifah, Nur; Barkah, Barkah; Marumpe, Dody Pratama (SEAN Institute, 2024)
This study investigates the influence of product innovation on purchasing decisions at PT Pegadaian, with brand image as the mediating variable. The study utilized a causal associative research design, and data was collected through the distribution of questionnaires using the Google Forms application. This study's population comprises PT Pegadaian customers who have previously conducted transactions with the company. A total of 235 respondents were chosen for the study utilizing non-probability sampling, namely the purposive sampling method. The collected data were subsequently analyzed using SEM AMOS 24. This study's primary conclusions suggest that product innovation and brand image positively and significantly influence purchase decisions at PT Pegadaian. Product innovation exerts a positive and significant influence on the brand image of PT Pegadaian. Meanwhile, brand image successfully mediates the effect of product innovation on purchase decisions at PT Pegadaian.